The Influence of Social Conflict, Cultural Diversity, and Tolerance on Social Integration in Urban Societies - Sudirman, Sudirman; Kalip, Kalip; Mulianingsih, Ferani; Usman, Muh Ilham (The Eastasouth Journal of Social Science and Humanities, 2025)
This study aims to examine the influence of social conflict, cultural diversity, and tolerance on social integration in urban communities. Using survey methods and multiple linear regression analysis, data were collected from 300 respondents living in urban areas with high levels of cultural diversity. The results show that social conflict has a significant negative effect on social integration, while cultural diversity and tolerance have a significant positive impact. Social conflict reduces the level of social cohesion and strengthens segregation, while cultural diversity and tolerance encourage social engagement and increase community harmony. These findings indicate the importance of policies that support conflict management and the promotion of diversity and tolerance as strategies for building a more integrated society in urban environments. This study also highlights the need for further research in other urban contexts to enrich the understanding of the dynamics of social integration.